Do Perceptions of Parental Goal Promotion and Autonomy Support Explain the Relationship between Generational Status and Academic Processes and Outcomes? - (:unkn) unknown (My University, 2012)
ABSTRACT

The term "first-generation" has long been used in the literature as a descriptive term to identify a subpopulation of college students who experience obstacles toward earning their degree in part because of the disadvantage of having neither parent/primary caregiver earn a four-year college degree. Prior research has identified "who" first-generation students are and the obstacles they face toward degree completion. However, less is known about the underlying factors which contribute toward the behaviors of first-generation students reported in the literature. Hierarchial multiple regression analyses were conducted to determine if a relationship exists between generational status, parental autonomy, and parental goal support, on one hand, and student aspirations, approaches to learning and GPA on the other. Participants were 890 undergraduate students who completed a booklet with five questionnaires. These questionnarires included a demographic questionnaire, Parental Goal Promotion Survey, Parental Autonomy Support Survey, Approaches to Study Inventory for Students (ASSIST) and an Aspiration Index. Analyses showed no differences between FG and NFG students on any of the above mentioned variables. Results of the study indicated that intrinsic parental goal promotion emerged as a statistically significant predictor of student intrinsic aspirations and strategic approaches to learning. Also, parental autonomy support was found to be a significant predictor of students' self-reported deep and strategic approaches to learning.
Keywords: First-generation college students--Psychology; Autonomy in youth; Goal (Psychology); Parent and adult child